Comprehensive Analysis of SMC Gene Family Prognostic Value and Immune Infiltration in Patients With Pancreatic Adenocarcinoma - Nie, Hui; Wu, Yanhao; Ou, Chunlin; He, Xiaoyun (Frontiers in Medicine, 2022)
Pancreatic adenocarcinoma (PAAD) is a malignant tumor with high morbidity and mortality worldwide. Members from the structural maintenance of chromosomes (SMC) gene family function as oncogenes in various tumor types, but their roles in PAAD have not been elucidated. In this study, we aimed to explore the role of the SMC family in tumor progression and cancer immune infiltration in PAAD using integrative bioinformatic analyses. The results showed that the SMC 1A, 2, 3, 4, and 6 were overexpressed in PAAD tissues; of these, SMC 1A, 4, 5, and 6 could be potential prognostic biomarkers for PAAD. The expression of SMC genes was found to be strongly associated with immune cell infiltration. According to the infiltrative status of various immune cells, the mRNA expression of SMC genes in PAAD was associated with the overall and recurrence-free survival of patients. In conclusion, the SMC gene family is associated with PAAD and may be involved in tumorigenesis and cancer-immune interactions; thus, members from this gene family may serve as promising prognostic and therapeutic biomarkers of PAAD.